2017
DOI: 10.7251/agren1601037b
|View full text |Cite
|
Sign up to set email alerts
|

Reducing and Total Sugar Content in Onion During Storage in the Republic of Macedonia

Abstract: In Macedonia, sweet onion landrace 'buchinska arshlama' is traditionally stored during winter period from October until April. The objective of this research was to determine the content of reducing sugar and total sugar in onion bulbs during storage period in a traditional way and in cold rooms. Every month, samples were taken for chemical analysis. The results were statistically processed and tested with t-test. The average reducing sugar content in onion stored in a traditional way was 4.8%, while the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Likewise, in the study by Lu et al ., it was observed that addition of onion powder to meatballs caused an increase in MeIQ content compared to the control group and the reason was explained by the Maillard reaction of carbohydrates (reducing sugar) in onion. Thus, it was reported that onion generally contains carbohydrate between 5.2% and 9% and majority (60–80%) of the dry substance content of onion is formed from non‐structural carbohydrates (glucose, fructose, sucrose and fructans) . It is known that the Maillard reaction plays an important role in the formation of IQ‐type HCAs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in the study by Lu et al ., it was observed that addition of onion powder to meatballs caused an increase in MeIQ content compared to the control group and the reason was explained by the Maillard reaction of carbohydrates (reducing sugar) in onion. Thus, it was reported that onion generally contains carbohydrate between 5.2% and 9% and majority (60–80%) of the dry substance content of onion is formed from non‐structural carbohydrates (glucose, fructose, sucrose and fructans) . It is known that the Maillard reaction plays an important role in the formation of IQ‐type HCAs .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it was reported that onion generally contains carbohydrate between 5.2% and 9% and majority (60-80%) of the dry substance content of onion is formed from non-structural carbohydrates (glucose, fructose, sucrose and fructans). 68 It is known that the Maillard reaction plays an important role in the formation of IQ-type HCAs. 69,70 Jägerstad et al 69 has reported that creatine, free amino acids and hexoses found in raw meat are precursors of IQ-type HCAs.…”
Section: Recoveries Limit Of Detection and Limit Of Quantification Vmentioning
confidence: 99%
“…The differences between the varieties and storage durations were found to be significant. The decreasing trend may be due to the conversion of reducing sugars to starch during storage at low temperatures (Kukanoor, 2005;Bogevska et al, 2016). It wasobserved that the cultivar, postharvest treatments, and temperature can affect sugar content during storage, showing either a constant or an unstable pattern (Chope et al, 2007).…”
Section: Sugar Contentmentioning
confidence: 99%
“…From a time period 2002 to 2011, the Food and Agriculture Organization of United Nations (FAOSTAT) also indicated that onion production escalated up to 85 million tons. Onion comprises of moisture (ranging from 88.6% to 92.8%), fat trace (0.2%), ash (0.6%), and carbohydrates (ranging from 5.2% to 9.1%) (Bogevska et al, 2016 ; Griffiths et al, 2002 ; Jiang et al, 2021 ). The majority of the compositional framework of onion comprises dry matter content having nonstructural carbohydrates, such as fructans, sucrose, fructose, and glucose (Li et al, 2020 ; Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The average sugar content of traditionally stored onion was reported to be 6%. Reducing sugar content of onion at cold room storage was 4.6% (Ameer, Shahbaz, & Kwon, 2017 ; Bogevska et al, 2016 ; Sharma, Ko, et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%